The Influence of Islamic Business Ethics on Consumer Satisfaction in Majenang Market - Safitri, Novia (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
The purpose of this study is to determine and analyze Islamic Business Ethics in Majenang Market and the influence of Islamic Business Ethics on Consumer Satisfaction. This type of research is quantitative research and the method used in this study is the survey method. The place that is the object of research is the Majenang Cilacap Market which is located at the Majenang main market, Sawah area, Sindangsari, Majenang District, Cilacap Regency, Central Java. The results of the partial t-test analysis of the Islamic business ethics variable on consumer satisfaction are proven by the calculated t of 6.404> t table of 0.68083 with a significant value of t count> t table or a significant value of 0.001> alpha 0.005 with a significant value of 0.0000 f table 4.10 with a significance level value of 0.000> 0.05 which means that Islamic business ethics (X) has a positive effect on consumer satisfaction. So the decision H0 is rejected and H1 is accepted.